Blippo and Beep - Weeks, Sarah; Ellis, Joey (Illustrator) (2022)
When robots Blippo and Beep share knock-knock jokes, Beep realizes Blippo does not understand how they work, and begins to run out of patience.
Ages 4-8.
Keywords: Robots -- Fiction; Friendship -- Fiction; Jokes -- Fiction; Picture books